Community Mobilization, Participation, and Blood Pressure Status in a Cardiovascular Health Awareness Program in Ontario. Issue 4 (March 2013) - Karwalajtys, Tina; Kaczorowski, Janusz; Chambers, Larry W.; Hall, Heather; McDonough, Beatrice; Dolovich, Lisa; Sebaldt, Rolf; Lohfeld, Lynne; Hutchison, Brian
Purpose: To determine the feasibility of a community-wide approach integrated with primary care (Cardiovascular Health Awareness Program [CHAP]) to promote monitoring of blood pressure (BP) and awareness of cardiovascular disease risk. Design: Demonstration project. Setting: Two midsized Ontario communities. Participants: Community-dwelling seniors. Intervention: CHAP sessions were offered in pharmacies and promoted to seniors using advertising and personalized letters from physicians. Trained volunteers measured BP, completed risk profiles, and provided risk-specific education materials. Method: We examined the distribution of risk factors among participants and predictors of multiple visits and elevated BP. Results: Opinion leaders aided recruitment of family physicians (n = 56/63) and pharmacists (n = 18/19). Over 90 volunteers were recruited. Invitations were mailed to 4394 seniors. Over 10 weeks, there were 4165 assessments of 2350 unique participants (approximately 30% of senior residents). 37.5% of attendees had untreated (16%; 360/2247) or uncontrolled (21.5%; 482/2247) high BP. Participants who received a letter (odds ratio [OR] 2.5, 95% confidence interval [CI] 2.1–3.0), had an initial elevated BP (OR 1.2, 95% CI 1.0–1.5), or reported current antihypertensive medication (OR 1.4, 95% CI 1.1–1.6) were more likely to attend multiple sessions (p ≤ .05 for all). Older age (≥ 70 years; OR 1.5, 95% CI 1.3–1.8), BMI ≥ 30 (OR 1.7, 95% CI 1.4–2.2), current antihypertensive medication (OR 1.6, 95% CI 1.3–1.9), and diabetes (OR 2.4, 95% CI 1.9–3.2) predicted elevated BP (p < .001 for all). Conclusion: The program yielded learning about community mobilization and identified a substantial number of seniors with undiagnosed/uncontrolled high BP.